Impact of tonsillectomy on COVID–19 pandemic: an observational study of the incidence and prognosis. (1st September 2021) - Kara, Ahmet; Elden, Halil; Okur, Engin; Yilmaz, Mahmut Sinan; Mutlu, Fuldem; Guven, Mehmet; Demir, Deniz
Abstract: Background: Due to many different reasons such as possible coronavirus colonization in tonsillar tissue, decreased enzymatic antiviral activity, decreased cytokine activity from palatine tonsil tissue and reduced humoral and cellular immune response, tonsillectomy may alter the incidence of Covid–19. Aims/Objectives: To reveal the frequency of Covid–19 in patients who underwent tonsillectomy and to analyze the effect of tonsillectomy on the severity of the disease. Materials and methods: Patients aged between 15 and 65 and had a history of tonsillectomy were compared with control group in terms of incidence and severity of Covid–19 disease. Results: A 4% Covid rRT–PCR test positivity rate was detected in patients with tonsillectomy whereas; it was 6.8% in the control group with a statistically significant difference. However, in terms of disease severity there was no difference between the two groups. Conclusions and significance: It has been proven that tonsillectomy surgery does not pose an additional risk in terms of COVID 19 disease severity. The positive effect of tonsillectomy in terms of disease frequency has been even demonstrated for the first time in the literature.